Crossmodal learning of target-context associations: When would tactile context predict visual search? - Chen, Siyi (Atten Percept Psychophys, 2019)
It is well established that statistical learning of visual target locations in relation to constantly positioned visual distractors facilitates visual search. In the present study, we investigated whether such a contextual-cueing effect would also work crossmodally, from touch onto vision. Participants responded to the orientation of a visual target singleton presented among seven homogenous visual distractors. Four tactile stimuli, two to different fingers of each hand, were presented either simultaneously with or prior to the visual stimuli. The identity of the stimulated fingers provided the crossmodal context cue: in half of the trials, a given visual target location was consistently paired with a given tactile configuration. The visual stimuli were presented above the unseen fingers, ensuring spatial correspondence between vision and touch. We found no evidence of crossmodal contextual cueing when the two sets of items (tactile, visual) were presented simultaneously (Experiment 1). However, a reliable crossmodal effect emerged when the tactile distractors preceded the onset of visual stimuli 700 ms (Experiment 2). But crossmodal cueing disappeared again when, after an initial learning phase, participants flipped their hands, making the tactile distractors appear at different positions in external space while their somatotopic positions remained unchanged (Experiment 3). In all experiments, participants were unable to explicitly discriminate learned from novel multisensory arrays. These findings indicate that search-facilitating context memory can be established across vision and touch. However, in order to guide visual search, the (predictive) tactile configurations must be remapped from their initial somatotopic into a common external representational format.